ELECTORAL HISTORY OF DISTRICT SARGODHA (1946-2013): AN OVERVIEW - Warda Kousar; Dr. Muhammad Waris; Dr. Hamid Iqbal (International Journal of Contemporary Issues in Social Sciences, 2024)
This article analyzes of the election dynamics and political transformations in the Sargodha district. This study examines the growth of political ideology, party dominance, and leadership patterns that had influenced Sargodha’s political environment during 1946-2013. It examines the initial post-independence years, characterized by the preeminence of the Muslim League and the reinforcement of local political power structures. The article examines the emergence of powerful local families and landlords during this period, whose patronage networks significantly influenced electoral results. This study examines how the political party affiliations and voter preferences were set in Sargodha during 1946-2013 and what kind of influence feudal and biradari (clan) systems exerted on electoral politics as well as local power structures? Whether the national political changes and affected electoral trends in the district? The study utilizes a historical-analytical approach, incorporating both primary and secondary sources. Election outcomes from the National and Provincial Assemblies, political biographies, and historical sources are examined to discern party’s patterns, voter conduct, and the impact of local elites. The study indicated considerable variations in party dominance over time during the early post-independence era. The Muslim League maintained a dominant position; however, this influence progressively yielded to local power elites who affiliated with several political parties over time. The 1970s signified a transition towards populism with the emergence of PPP and from the 1980s onwards, PML-N ascended as a preeminent entity, using regional feudal connections and religious sentiments. The study elucidates the intricate relationship between local power structures in election history of Sargodha.